Frictional Properties of the TiNbTaZrO Orthodontic Wire—A Laboratory Comparison to Popular Archwires - Krzysztof Schmeidl (MDPI AG, 2021)
Background. This study aimed to determine the kinetic frictional force (FF) of the recently produced TiNbTaZrO (Gummetal) orthodontic wire and compare it to the widely used wires of stainless steel (SS), nickel-titanium (NiTi), cobalt-chromium (CoCr) and titanium-molybdenum (TiMo) alloys. Methods. Five types of 0.016″ × 0.022″ wires were ligated with elastic ligatures to 0.018″ × 0.025″ SS brackets. The dynamic FFs between the brackets and ligated wires were measured utilizing a specialized tensile tester machine. Prior sample sizes for different archwires were conducted using power analysis for the general linear models. The existence of significant differences in FF between examined materials was initially confirmed by the one-way analysis of variance (ANOVA) with further evidence of pairwise differences by Tukey’s Honest Significant Difference test. Results. The pairwise differences between means of kinetic FFs for NiTi, CoCr, and Gummetal wires were not statistically significant (adjusted p-value > 0.05). Stainless steel alloy presented the lowest FF values significantly different from other groups (adjusted p-value < 0.05). On the contrary, TiMo wires showed significantly greater FFs (adjusted p-value < 0.05) than other alloys. Conclusions. Gummetal orthodontic wire exhibits similar frictional resistance as NiTi and CoCr wires. Bendable TiNbTaZrO wire might be used for sliding mechanics due to its favorable frictional properties.